ANALISIS PERBANDINGAN MONITORING JARINGAN MENGGUNAKAN CACTI DENGAN LIBRENMS DI PT. PROXI JARINGAN NUSANTARA CABANG SUKABUMI - Putri, Ditia Mutiara; Thohir, Muhammad Ikhsan (MAJU : Indonesian Journal of Community Empowerment, 2025)
This internship activity aims to analyze two network monitoring systems, namely Cacti and LibreNMS, used at PT. Proxi Jaringan Nusantara, Sukabumi. The methods used include observation, interviews, and literature study. The results show that Cacti excels in graphical visualization and resource efficiency, while LibreNMS is superior in automation features and device detection. In conclusion, each tool has its advantages depending on network monitoring needs.